Mantra Sebagai Ide Penciptaan Musik Etnis Jampi - Gigih Ovra Wulanda (SELONDING, 2018)
Mantra is the title of a musical work with spells of West Kalimantan ethnic Malays as the main material for its work. The purpose of this composition is to express spell duality. The concept of duality here is a mantra that is useful as a medium of goodness and a second mantra as a medium for danger. The word mantra itself can be interpreted as words when spoken containing mystic or sacred.Through the stages of exploration, improvisation, until finally the process of explicitly forming spells of musical composition can be seen as a form of music that has three parts. Covers the beginning, middle and end. This composition is played by two different idioms including ethnic musical instruments and ethnic Javanese musical instruments. Keywords: dualism, spells, Malay, mystical